2018
DOI: 10.1186/s12917-018-1708-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and parasites in Podarcis sicula and P. sicula klemmerii

Abstract: BackgroundNew epidemiological data on bacterial and parasitic infections in 24 Italian wall lizards, namely Podarcis sicula (mainland population) and P. sicula klemmerii (insular population) in southern Italy were provided. To achieve this goal, samples were collected from individuals belonging to the two populations and analysed by microbiological and parasitological methods.ResultsA wide range of bacteria (e.g. Pantoea spp., Citrobacter spp., Morganella spp., Pseudomonas, Enterobacter spp., Staphylococcus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Bao and co-workers reported an increase in Eisenbergiella after infection by Echinococcus granulosus in mice 53 . Furthermore, Dipineto and collaborators, analysing parasites in lizard populations on mainland and island from the same as our study area, showed the presence of Coccidae only in faeces of island lizards 54 . Interestingly, our results indicated that the relative abundance of Eisenbergiella is significantly greater in the microbiota of IL than MA.…”
Section: Discussionsupporting
confidence: 60%
“…Bao and co-workers reported an increase in Eisenbergiella after infection by Echinococcus granulosus in mice 53 . Furthermore, Dipineto and collaborators, analysing parasites in lizard populations on mainland and island from the same as our study area, showed the presence of Coccidae only in faeces of island lizards 54 . Interestingly, our results indicated that the relative abundance of Eisenbergiella is significantly greater in the microbiota of IL than MA.…”
Section: Discussionsupporting
confidence: 60%
“…in different types of lizards is highly variable, with values of 6.2% in the case of the wall gecko (Hemydactilus turcius) in Iraq [80], 33.3% in Agama agama Linnaeus 1758 in Nigeria [89], 25.0% in Gallotia intermedia, and 11.1% in Gallotia bravoana in the Canary Islands, Spain [80], or 41.7% in Podarcis sp. Wagler, 1830 in Italy [90]. In the case of the population of Anolis sp.…”
Section: Pseudomonas Spmentioning
confidence: 99%